The contribution of languages of Muslim-majority speakers to English vocabulary - Mohamed Ali, Haja Mohideen; Mohideen, Shamimah (Asian Economic and Social Society, 2012)
The English language owes a debt of gratitude to numerous languages, those with whom the British colonizers came into contact through colonization and trade, and also with those whose languages are spoken by a large number of people. Examples of the former are Bengali, Hindi, Hausa, Malay and Urdu. The examples of the latter are Arabic, Mandarin, Persian and Turkish. When we think of the Muslim contribution to the vocabulary of English, it is mostly Arabic, Persian and Turkish that comes to one‟s mind. Not much is known about the lexical items from Swahili, Fulani, Wolof and Tatar, for instance. This study is an attempt to discover the various vocabulary items from languages of Muslim-majority speakers that have found their way into the international lingua franca and thus used internationally and regionally. Their use is authenticated through influential dictionaries and online content. A sizeable number of such words have indeed become part of English and are used in the print and electronic media. These words, though from the sources of Muslim-majority languages are used by both speakers who use English as their primary and secondary language. These words fill a lexical gap experienced in the English language which has only become richer, not poorer, by lexical borrowing of the languages in question.